María como arquetipo de libertad: Un análisis de la evolución histórica de las advocaciones de la Virgen - Moreno Almárcegui, Antonio (Cauriensia, 2023)
This article analyzes the evolution of iconography associated with the Virgin Mary in Spain. It does so by studying Marian invocations in more than a thousand Marian sanctuaries and hermitages from between the fifth and nineteenth centuries. Although topographic invocations predominated in the early years, from the fourteenth to the sixteenth centuries, personal invocations that present Mary as a model or mediator between God and men began to predominate. Finally, from the seventeenth century onward, invocations that present Mary as a powerful intercessor began to gain strength. This is so especially in larger cities dominated by a commercial logic that presents Mary’s will as an archetype of contractual freedom, i.e., that which gives rise to consent. We suggest that this development of mercantile logic tended to displace the rationality proper to the logic of the gift, especially of the maternal gift that Mary embodied.